Causal relationship between sugar prices, imported sun flower oil, crude oil prices and the exchange rate of the Iraqi dinar - العبدلي, سعد عبد نجم; سليمان, هيفاء يوسف (Journal of Economics and Administrative Sciences, 2018)
AbstractThe increasing of some traded Agricultural crops prices coincide with the increasing of crude oil prices in global market since the beginning of 21st century which indicate the possibility of short run and long run causality relation between the imported economic variables. The study aims to analysis the causality effects between some of Agricultural crops prices imported by Iraq and the prices of crude oil and Iraq dinar exchange rate   in global markets for period (2004:1 -2016:4) theory for developing the adequate price and economic police for Iraqi economic sector. The results show the existence of short- run and long- run between the economic variable go form crude oil prices to agricultural crops prices.